2020
DOI: 10.1038/s41598-020-59153-6
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in cause-specific mortality and transition to renal replacement therapy among patients with end-stage renal disease

Abstract: Despite some studies showing seasonal variations in mortality and the transition to renal replacement therapy in patients with end-stage renal disease, detailed evidence is still scarce. We investigated seasonal variations in patients with end-stage renal disease using a large Japanese database for dialysis patients. We compared the fractions of all-cause and cause-specific mortality and the transition to renal replacement therapy among seasons and performed a mixed-effects Poisson regression analysis to compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 29 publications
(51 reference statements)
1
13
2
Order By: Relevance
“…Annual trends in 2013 to 2019 display a well-known seasonal pattern, with peaks in late January and early February. 37 , 38 , 39 , 40 Beginning in 2020, deviations from this trend were commensurate with known waves of the COVID-19 pandemic ( Figure 1 A). Historically, Black patients receiving dialysis have had significantly lower mortality than non-Black patients in the US.…”
Section: Resultssupporting
confidence: 63%
“…Annual trends in 2013 to 2019 display a well-known seasonal pattern, with peaks in late January and early February. 37 , 38 , 39 , 40 Beginning in 2020, deviations from this trend were commensurate with known waves of the COVID-19 pandemic ( Figure 1 A). Historically, Black patients receiving dialysis have had significantly lower mortality than non-Black patients in the US.…”
Section: Resultssupporting
confidence: 63%
“…Iseki et al reported a strong correlation between the transition for hemodialysis and ambient air temperature in patients with chronic renal failure in Okinawa, Japan [11]. Goto et al also found that the initiation of hemodialysis was the highest in winter and the lowest in summer [12].…”
Section: Discussionmentioning
confidence: 98%
“…Many factors have been reported to affect renal failure [4][5][6][7]. Environmental factors, such as air temperature parameters, have been associated with the number of deaths due to renal failure [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the superior mechanisms that have developed during evolution to protect hibernating bears from the dramatic physiological transitions that occur between periods of high and low metabolic activity, other seasonal mammals, such as lemurs, are at higher risk, when the number of seasonal transitions increased in frequency [45]. Such studies may be of relevance for climate-induced seasonal shift and increase reasons for seasonal variation in mortality observed in burden of lifestyle diseases, such as CKD [46] and stroke [47].…”
Section: Hibernation and Seasonal Variability Hold Clues For Human Healthmentioning
confidence: 99%